Critical Discourse Analysis towards Authority Ideology "Case of Mega Corruption E-KTP (Electronic ID Card) " in Tempo Magazine - Martono Martono; Sri Mulyani (JETL (Journal of Education, Teaching and Learning), 2018)
The ideology that is reflected in the discourse of Tempo Magazine in 2017 'the case of Mega Corruption e-KTP is seen from the text structure which includes the macrostructure. The global meanings studied are interrelated. The data obtained by journalists are used to discuss the topic of e-KTP case. "Fireball Corruption KTP". Superstructure discourse discussed based on the introduction, the contents, the cover, but not found conclusions. The preliminary section described has always supported the title of the discourse. The content section is the focus of journalist's study on e-KTP corruption issues. The closing section used by journalists always gives a settlement of the news presented. The microstructure of the discourse uses effective, straightforward and diction sentences. Ideology is seen from social cognition. There is a linkage of texts that journalists describe with the community. All perceptions and actions, and ultimately the production and interpretation of this discourse are based on the mental representation of every event that takes place. Events are presented based on a lot of evidence and believed to be true. Ideology is seen from the social context that includes the practice of power and access to affect the discourse. The practice of power in the discourse on the topic of mega corruption is related to the members of the People's Legislative Assembly and the Chief Judge of the Court. The Chief Justice used his power to reprimand the accused. Judging from the access that influences discourse then found a character who can use and or influence the discourse.